Optical and structural properties of AlN ceramics irradiated with C2+ ions - Gladkikh, T.; Kozlovskiy, A.; Kenzhina, I.; Kanuikov, E.; Zdorovets, M. (Recent Contributions to Physics, 2019)
Resistance to high doses of radiation is one of the important factors of applicability of functional ceramic materials in future thermonuclear reactors. Also, nitride materials (BN, AlN, Si3N4) are considered as the most suitable candidates for the development of optical and diagnostic windows, insulation materials, reactor walls. The effect of irradiation with C2+ ions on changes in optical and structural properties of AlN-based ceramics has been studied. The choice of C2+ ions is due to the possibility of modeling defects formation in the surface layers, as well as the formation of carbide phases in the structure during irradiation. According to XRD data, the formation of an impurity phase characteristic of the Rhombohedral Al4C3 is observed in the structure of irradiated samples, the presence of which is due to the implantation of carbon ions into the surface layers of not more than 150 nm. The decrease in the intensity of the TSL spectrum for irradiated samples is due to the appearance of defects, as well as an increase in the concentration of impurity atoms. That leads to the substitution of Al and N atoms in the structure. At the irradiation dose of 1015 ion/cm2, there is a sharp increase in the absorption spectrum and the magnitude of the optical absorption.